Prediction of neurological outcome after moderate head trauma computed tomography versus a Serum biomarker fatty acid binding protein - Dr. Hany Kamal Michail,; Ibrahim Abbas Yossef,; Rehab Mohammed AbdElaalSayed,; Dr.Tamer El Zaeem Esmaeel,; Dr.Wegdan Abdel Rahman Ali, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Traumatic brain injury (TBI) is a major public health challenge, causing long-term disability and dependency. Computed tomography (CT) remains the diagnostic gold standard but poses risks such as radiation exposure and high costs. Heart-type fatty acid-binding protein (H-FABP) has emerged as a potential biomarker for brain and cardiac injuries. This study evaluates H-FABP's utility in predicting neurological outcomes following moderate TBI. Methods: A prospective controlled trial was conducted at Minia University Hospital on 30 critically ill adult patients with moderate TBI (GCS 9–12). Patients were assessed using Advanced Trauma Life Support protocols, clinical scores (APACHE II, SOFA), and CT imaging classified by Marshall and Rotterdam scales. Serum H-FABP levels were measured at admission, 24, and 72 hours post-injury using electrochemoluminometric immunoassays. Data analysis included ROC curves, correlation studies, and statistical comparisons of CT findings and H-FABP levels. Results: H-FABP levels significantly increased at 24 hours post-injury (mean: 2.85±0.89 ng/mL) compared to admission (1.86±0.58 ng/mL, p<0.001) and remained elevated at 72 hours. Positive correlations were observed between H-FABP levels and Marshall CT scores at 24 and 72 hours (r=0.50, 0.53; p<0.05). H-FABP showed a sensitivity of 100% and specificity of 87% at a cut-off value >2.45 ng/mL for predicting poor neurological outcomes. Conclusion: H-FABP is a promising biomarker for predicting outcomes in moderate TBI, potentially reducing unnecessary CT scans, radiation exposure and costs. Further studies are needed to assess its utility across varying TBI severities and in biomarker panels for comprehensive diagnostics.